Correlation between anterior knee pain with flexibility muscles hip - Borges, Natália Faria; Borges, Beatriz Santana; Sanchez, Eliane Gouveia de Morais; Sanchez, Hugo Machado (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The patellofemoral pain syndrome (PFPS) is one of the most common affections of the knee joints that has as one of its main functions the human locomotion, while the hip is the largest spherical joint of the human body. Objective: To know the correlation of anterior knee pain with hip flexibility and range of motion (ROM) in female academics. Method: A cross-sectional descriptive study was carried out with a population composed by 40 academics, divided into 2 groups of equal size, one composed by volunteers with PFPS and the other without the syndrome. The volunteers were aged between 18 and 30 years. For flexibility and ROM evaluation was used a fleximeter and a universal goniometer, respectively. Results: After statistical analysis, it was verified that the ROM of the hip abduction was decreased in the PFPS group, probably due to the retraction of the adductor muscles of the hip, or even by the loss of the muscular strength of them. With regard to flexibility, hip flexor muscles were retracted, with a significant difference comparing the group with pain and the group without anterior knee pain. Conclusion: It was shown that there are muscle changes related to flexibility and ROM in the flexor and hip abductor groups, respectively, in the volunteers with presence of Patellofemoral Pain Syndrome.